Acoustic modeling of micro-lattices obtained by additive manufacturing. (July 2020) - Boulvert, Jean; Costa-Baptista, Josué; Cavalieri, Théo; Perna, Maxime; Fotsing, Edith Roland; Romero-García, Vicente; Gabard, Gwénaël; Ross, Annie; Mardjono, Jacky; Groby, Jean-Philippe
Abstract: The acoustic behavior of 3D printed micro-lattices is investigated to assess the impact of defects induced by the Fused Deposition Modeling technique on the parameters of the equivalent fluid medium. It is shown that the manufacturing process leads to three types of non-trivial defects: elliptical filament section, filament section shrinkage and filament surface rugosity. Not considering these defects may lead to acoustic predictions errors such as an underestimation of around 0.1 of the rigid backing absorption coefficient. Inverse characterization of seven homogeneous samples allows to fit the acoustic prediction model considering this kind of defects.